Enhanced performance in fusion plasmas through turbulence suppression by megaelectronvolt ions - Zarzoso, D.; Benkadda, S.; Akhtar, M.; Alessi, E.; Ariola, M.; Begolli, A.; Bernardo, J.; Bishop, H.; Blanchard, P.; Bohm, P.; Brix, M.; Buermans, J.; et al. (Nature Physics, 2022)
Alpha particles with energies on the order of megaelectronvolts will be the main source of plasma heating in future magnetic confinement fusion reactors. Instead of heating fuel ions, most of the energy of alpha particles is transferred to electrons in the plasma. Furthermore, alpha particles can also excite Alfvénic instabilities, which were previously considered to be detrimental to the performance of the fusion device. Here we report improved thermal ion confinement in the presence of megaelectronvolts ions and strong fast ion-driven Alfvénic instabilities in recent experiments on the Joint European Torus. Detailed transport analysis of these experiments reveals turbulence suppression through a complex multi-scale mechanism that generates large-scale zonal flows. This holds promise for more economical operation of fusion reactors with dominant alpha particle heating and ultimately cheaper fusion electricity. Experiments at the Joint European Torus tokamak show improved thermal ion confinement in the presence of highly energetic ions and Alfvénic instabilities in the plasma.